Self-Blame and Tension Reduction: Self-Criticism Stability Study on The Students (Future Science, 2022)
Anxiety and stress are still a massive conversation on the academic scope. One of the factors in it is self-criticism. The main effort to control it is done by coping with stress. There are two types of stress coping used by students, namely self-blame and tension reduction. However, the influence and relationship between both are still debated clinically and psychologically. The purpose of this study was to determine how the influence of self-blame and tension reduction clinically and psychologically on students' self-criticism. We invited 304 students in Makassar (P=231, L=73). Data were collected using the self-criticism scale and The Ways of Coping (Revised) scale and analyzed using multiple regression techniques. The results of the study found that simultaneously self-blame and tension reduction affected the stability of students' self-criticism (p < 0.05). From this, we know that self-blame and tension reduction as stress-coping techniques have a greater effect when used together. These results give rise to a new schema for the stability of self-criticism and mental health. In the future, we suggest an in-depth review of the forms of negative associations of the tension reduction type in Indonesian students.